Effects of Aerobic and Resistance Exercise on Cardiovascular Parameters for People Living With HIV: A Meta-analysis. (March 2019) - Zech, Philipp; Pérez-Chaparro, Camilo; Schuch, Felipe; Wolfarth, Bernd; Rapp, Michael; Heissel, Andreas
Abstract : Abstract: People living with HIV (PLWH) have limited exercise capacity because of anemia, neuromuscular disorders, and pulmonary limitations. We used a meta-analysis to examine the effect of aerobic and resistance exercise alone and in combination on cardiovascular parameters. Subgroup meta-analyses were conducted and long-term effects of exercise were investigated. A systematic literature search was conducted up to July/August 2017. The Physiotherapy Evidence Database-scale was used to rate quality and assess the risk of bias on the papers. Standardized mean differences (SMDs) were calculated to assess the effect of exercise. Posttreatment comparison between the exercise and control groups revealed moderate and large effect sizes in favor of the intervention group for VO2max (SMD = 0.66, p < .0001) and the 6-minute walk test (SMD = 1.11, p = .0001). Exercise had a positive effect on cardiovascular parameters in PLWH. Exercise can be a prevention factor for PLWH dealing with multiple comorbidities.